An Examination of The Protagonist in Pidi Baiq's Novel Dilan: Dia Adalah Dilanku 1991 - Suparni, Suparni; Ratnaningsih, Ratnaningsih (Yayasan Kyadiren, 2022)
Novels are fictional stories that are created by human reflection on the environment and experiences. Within a novel, the author uses their aesthetic experience and creativity to arrange storylines and characters. Examining the characters within a contemporary novel can be intriguing as the main character may reflect the author's idealism and response to their own life. With this in mind, the researcher analyzes the novel